Franco’s Regime and Galician Literature: Non chores, Sabeliña, the first Galician Literary Work during the Postwar Period. Between the populism and the “rexoubeirismo” - Pardo de Neyra, Xulio (Madrygal. Revista de Estudios Gallegos, 2015)
This study, written from a philological and didactic perspective, depicts a thorough analysis on creation and reception of Non Chores, Sabeliña, the first written work published in Galicia after the Spanish Civil War. This work has never been studied or analysed before, therefore it is a very original approach to Galician and Portuguese philology as well as Galician language and literature didactics.